2020
DOI: 10.1155/2020/5906901
|View full text |Cite
|
Sign up to set email alerts
|

Research on Risk Diffusion Mechanism of Logistics Service Supply Chain in Urgent Scenarios

Abstract: Although there are some studies on the risk management of logistics service supply chain (LSSC), we still know little about the effects of risk evolution and interactional mechanism of subjects in different urgent scenarios of logistics service supply chain from a micro perspective. Based on the structures of the LSSC, this study thus analyzed the risk evolution and the main actors’ reactions in the LSSC, including categorizing the urgent scenarios, analyzing their impacts on the diffusion intensity of pricing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Liu et al [10] studied the impacts of loss-averse preference on the service capacity procurement decisions with demand updating in a logistics service supply chain, which consists of one logistics service integrator and one functional logistics service provider. Zhang et al [11] analyzed the risk evolution and the main actors' reactions in the LSSC, including categorizing the urgent scenarios, analyzing their impacts on the diffusion intensity of pricing, profit, and demand, and verifying the models' validity with the numerical analysis. Lou et al [12] studied the choice of logistics service outsourcing in the retailer-led supply chain and found that when retailers share part of the fixed cost, a win-win situation will be achieved.…”
Section: Coordination Of Logistics Service Supply Chainmentioning
confidence: 99%
“…Liu et al [10] studied the impacts of loss-averse preference on the service capacity procurement decisions with demand updating in a logistics service supply chain, which consists of one logistics service integrator and one functional logistics service provider. Zhang et al [11] analyzed the risk evolution and the main actors' reactions in the LSSC, including categorizing the urgent scenarios, analyzing their impacts on the diffusion intensity of pricing, profit, and demand, and verifying the models' validity with the numerical analysis. Lou et al [12] studied the choice of logistics service outsourcing in the retailer-led supply chain and found that when retailers share part of the fixed cost, a win-win situation will be achieved.…”
Section: Coordination Of Logistics Service Supply Chainmentioning
confidence: 99%
“…Sustainability 2022, 14, 8420 4 of 15 (2) Each node i becomes active with probability b i (t), and it forms m hyperedges with d nodes selected by Equation (2). The inactive nodes can also receive connections.…”
Section: Activity-driven Networkmentioning
confidence: 99%
“…Risks will not only make the entire supply chain unstable but also cause companies to suffer substantial financial losses. Therefore, understanding the risk diffusion mechanism of the supply chain network [2] and taking effective measures to suppress it is of great significance to the stability of the entire market and social progress [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the complex network theory, Ma et al constructed an improved structure model of logistics service supply chain, reconstructed the operation mechanism of logistics service supply chain, determined the vulnerable nodes in logistics service, and clarified the vulnerable mechanism of logistics service center [25]. Based on the structure of logistics service supply chain, Guangsheng Zhang et al analyzed the evolution of risk and the reactions of major actors [26]. Wang et al established a nonlinear mixed integer multiobjective optimization model for service providers selection and order assignment in mass customization logistics service mode and designed an improved genetic algorithm based on the multilayer coding technique to solve the model [27].…”
Section: Service Supply Chainmentioning
confidence: 99%